Optical Interferometric Properties of Porous Anodic Alumina Nanostructures. (2016) - Choudhari, K.S.; Sangeeth, K.; Kulkarni, Suresh D.; Chidangil, Santhosh
Abstract: Highly ordered porous anodic alumina nanostructures (PAA) with tunable pore properties have been prepared by electrochemical anodization. The PAA nanostructures were prepared in oxalic acid electrolyte at anelectrochemical potential of DC 40 V. The surface morphology of prepared PAA was examined using scanning electron microscopy (SEM) and atomic force microscopy (AFM). The results showed that the nanoporous structures have hexagonally arranged and highly ordered pore arrays with the pore diameters of about50 nm and interpore distance of 100 nm. The optical reflective interference spectroscopic properties of PAA were recorded in the wavelength range of 400 – 900 nm. The reflective spectra of PAA were used for the thickness measurements. It was observed that the pore properties of PAA varied with the applied voltage leading to changes in the interference pattern and in turn changes in the effective optical thickness (EOT) of the substrates. PAA having regular pore structure arrangement with optical reflective Interferometric spectroscopy find potential applications as reliable technique for optical biosensing, heavy and toxic metal ion detection for environmental control etc.